Analysis Of The Effectiveness Of Regional Revenue And Expenditure Budget Management (APBD) In Improving Regional Financial Performance In Bengkulu Province - Desita Rahayu; Kurnia Cahya Saputri; Dion Berry (International Journal of Social and Management Studies, 2026)
This study aims to analyze the effectiveness of Regional Revenue and Expenditure Budget (APBD) management in improving regional financial performance in Bengkulu Province. The approach used is qualitative with descriptive methods through literature study and document analysis, utilizing secondary data from scientific journals, regional financial reports, and literature related to public financial management. The results of the study indicate that the effectiveness of APBD management in Bengkulu Province is still not optimal, especially in terms of policy accuracy, implementation accuracy, and program target accuracy. In addition, the regional expenditure structure, which is still dominated by operational expenditures rather than capital expenditures, is one of the causes of the low quality of development output produced. The high budget realization does not fully reflect substantive success in improving community welfare, thus indicating a gap between administrative achievements and the actual impact of policies. This condition indicates the need for improvements in the regional financial management system. Therefore, increasing the effectiveness of the APBD needs to be done through strengthening performance-based planning, increasing transparency and accountability, and optimizing local revenue sources to support more sustainable and targeted development.